The Prevalence and Determinants of Fusidic Acid Resistance Among Methicillin-Resistant Staphylococcus aureus Clinical Isolates in China - Zhao, Huilin; Wang, Xinyi; Wang, Bingjie; Xu, Yanlei; Rao, Lulin; Wan, Baoshan; Guo, Yinjuan; Wu, Xiaocui; Yu, Jingyi; Chen, Liang; Li, Meilan; Yu, Fangyou (Frontiers in Medicine, 2021)
The significant increase in resistance of methicillin-resistant Staphylococcus aureus (MRSA) to fusidic acid (FA) is a worrying public concern. However, the data on the prevalence of FA-resistant MRSA isolates in China is still limited. This study aims to investigate the prevalence of FA resistance and resistance determinants among MRSA isolates from 6 tertiary hospitals in different regions of China between 2016 and 2020. The antimicrobial susceptibility of MRSA isolates was performed by disk diffusion test and broth microdilution method. And whole-genome sequencing was conducted to evaluate the determinants of FA resistance and molecular characterization of FA-resistant MRSA isolates. In this study, a total of 74 (74/457, 16.2%) isolates were identified to be FA-resistant among 457 non-duplicate MRSA isolates. The prevalence of 74 FA-resistant isolates was as follows: Hubei (28/70, 40%), Shanghai (18/84, 21.4%), Jiangxi (7/58, 12.1%), Inner Mongolia Autonomous Region (6/38, 15.8%), Guangdong (12/112, 10.7%), Sichuan (3/95, 3.2%). The mutations in fusA were present in 79.7% (59/74) of FA-resistant MRSA isolates, with 54 (54/74, 73%) with L461K mutation and conferring high-level resistance (MIC> 128μg/ml). Acquired gene, fusB, with low-level resistance (MIC< 16μg/ml) was found in 20.3% (15/74) FA-resistant MRSA isolates. ST5-MRSA-II-t2460 was the most prevalence clone with high-level resistance, accounting for 51.4% (38/74), which distributed in Hubei (24/28, 85.7%), Inner Mongolia Autonomous Region (4/6, 66.7%), Shanghai (7/18, 38.9%), and Guangdong (3/12, 25%). ST630-t4549 MRSA isolates with low-level resistance were the most common in Jiangxi (3/7, 42.9%) and Sichuan (2/3, 66.7%). In briefly, the prevalence of FA resistance among MRSA isolates in China was relatively high with geographic differences. High-level FA resistance was associated mostly with fusA mutations, especially the L461K mutation, while fusB usually conferred the low-level resistance to FA. The spread of ST5-MRSA-II-t2460 clone with high-level resistance to FA contributed greatly to the increase of FA-resistant MRSA isolates in most regions, especially in Hubei.